Developing a Multi-Dimensional Measure of Hotel Brand Customers' Online Engagement Behaviors to Capture Non-Transactional Value. (March 2023) - Shin, Hakseung; Perdue, Richard R.
While the historical focus of customer value research has been on transactional values, it is important to also understand the non-transactional values co-created by customer online engagement behaviors. However, online engagement research in tourism has focused almost exclusively on experience sharing behaviors via online review websites. This research is purposed to develop a multi-dimensional measure of non-transactional values created via online brand community members' engagement behaviors. Focusing on Marriott Bonvoy Insider Brand Community members, scale development procedures were used to identify four dimensions of non-transactional value: influential-experience value, C-to-B innovation value, relational value, and functional value. The scale achieves good validity and reliability. Relationships with both antecedents (e.g., internal and external motivations) and consequences (e.g., brand attachment and brand loyalty) were examined to assess nomological validity. Tourism researchers and managers can employ this scale to diagnose the non-transactional values co-created by customer online engagement behaviors.